The Clinical Efficacy and Adverse Effects of Interferon Combined with Matrine in Chronic hepatitis B: A Systematic Review and Meta‐Analysis. (6th April 2017) - Wang, Xiaotong; Lin, Haixiong; Zhang, Ren
Abstract : Currently, many studies have demonstrated certain beneficial effects of interferon (IFN) combined with matrine (Mat) for chronic hepatitis B (CHB) in China. However, the evidence from these randomized control trials is still controversial. Therefore, the aim of this meta‐analysis was to explore the efficacy and safety of Mat combined with IFN for CHB. We performed a systematic search of seven databases to identify all randomized controlled trials that treated CHB with IFN or IFN plus Mat from their start date to September 30, 2015. The clinical efficacy and adverse effects were evaluated. Nine studies involving 1089 participants were included. Compared with IFN monotherapy, IFN 5 MU combined with Mat 150 mg augmented the hepatitis B e‐antigen negative conversion rate after 3‐month treatment [relative ratio (RR) = 1.41; 95% confidence interval (CI) (1.18, 1.69), p  = 0.0002] and after 12‐month treatment [RR = 1.96; 95% CI (1.21, 3.19), p  = 0.006], hepatitis B virus DNA negative conversion rate after 3‐month treatment [RR = 1.37; 95% CI (1.16, 1.62), p  = 0.0002] and after 12‐month treatment [RR = 1.96; 95% CI (1.21, 3.19), p  = 0.006], hepatitis B virus e antibody (anti‐HBe) conversion rate after 3‐month treatment [RR = 1.47; 95% CI (1.19, 1.81), p  = 0.0003], and AST level after 3‐week treatment [weighted mean difference = −22; 95% CI (−40.41, −3.59), p  = 0.02]. Furthermore, IFN 3 MU 3 months combined with Mat 150 mg after 2‐month treatment reduced the risk of leucopenia and thrombocytopenia [RR = 0.55; 95% CI (0.36, 0.85), p  = 0.007]. Unfortunately, all of the included trials were not in favor of hepatitis B surface antigen (HBsAg) negative conversion rate or influenza‐like symptoms. Combination therapy with IFN plus Mat exhibited better clinical efficacy and fewer adverse effects than did IFN monotherapy in patients with CHB, except in the improvement of HBsAg negative conversion rate and influenza‐like symptoms. Given the poor methodological quality of the evidence currently available, future high‐quality, three‐blinded randomized control trials are necessary to confirm these results. Copyright © 2017 John Wiley & Sons, Ltd.